Designing an innovative pedagogy for sustainable development in higher education - Brinia, Vasiliki; Davim, J. Paulo (Higher education and sustainability, 2020)
"This book develops a "green pedagogy" and a mindset in Higher Education by using approaches based on innovative design thinking, arts-based practices, digital transformation, and entrepreneurship for sustainable development. New pedagogical methods and educational solutions are developed throughout the book to offer pedagogical support both to students and university/college level instructors"--